2015
DOI: 10.1007/s00384-015-2357-9
|View full text |Cite
|
Sign up to set email alerts
|

The size of retrieved lymph nodes correlates with the number of retrieved lymph nodes and is an independent prognostic factor in patients with stage II colon cancer

Abstract: PurposeIn stage II colon cancer, patients with many retrieved lymph nodes (LNs) have been reported to have better oncological outcomes. We tested the hypothesis that the greater number of retrieved LNs is related to a larger LN size.MethodsThe subjects comprised 320 patients with stage II colon cancer who underwent curative resection. All operations were elective and were performed by the same surgeons. The maximum long axis and short axis diameters of LNs were measured on hematoxylin-eosin-stained specimens.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We addressed this issue in a recently published study [16] and were able to show such an effect in colon cancer cases withconventional lymphnode dissectiontechnique.InpT3/ 4 stages, a significant outcome difference was found among the subgroups with high, low, and very low numbers of lymph node diameters <5 mm [16]. Okada et al report similar results when investigating conventionally dissected colon cancer cases [32]. In this context, it is important to mention that many authors demand substantially improved lymph node yields, and as a result, the numbers of retrieved lymph nodes have continuously increased over time [33].…”
Section: Discussionmentioning
confidence: 80%
“…We addressed this issue in a recently published study [16] and were able to show such an effect in colon cancer cases withconventional lymphnode dissectiontechnique.InpT3/ 4 stages, a significant outcome difference was found among the subgroups with high, low, and very low numbers of lymph node diameters <5 mm [16]. Okada et al report similar results when investigating conventionally dissected colon cancer cases [32]. In this context, it is important to mention that many authors demand substantially improved lymph node yields, and as a result, the numbers of retrieved lymph nodes have continuously increased over time [33].…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it seems to be a relevant morphologic adjunctive factor that reflects a certain molecular feature that promotes tumor progression. Lymph node size is the most recently introduced prognostic factor and is associated with lymph node yield and outcome [11,36]. Our group demonstrated that the paucity of lymph nodes with diameters >5 mm, termed LN5vl, is an independent prognostic factor in conventional lymph node dissected colon cancer [10] and after employment of advanced dissection techniques.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to the size of the imaging LNs, the pathological size of LNs may also be an indicator of the prognosis of colon cancer. Some studies of the prognostic value of LN size in early colon cancer suggested that LN enlargement was a favourable prognostic factor (by measuring LN size in pathological sections) . Markl et al found that patients with pT3/4 colon cancers with more retrieved LNs larger than or equal to 5 mm had longer median survival times.…”
Section: Discussionmentioning
confidence: 99%